Daptomycin is safe and effective for the treatment of gram‐positive cocci infections in solid organ transplantation. Issue 4 (19th May 2014) - Len, O.; Montejo, M.; Cervera, C.; Fariñas, M.C.; Sabé, N.; Ramos, A.; Cordero, E.; Torre‐Cisneros, J.; Martín‐Dávila, P.; Azanza, J.R.; Pahissa, A.; Gavaldà, J.; et al.
Abstract Introduction Infections caused by resistant gram‐positive cocci (GPC), especially to glycopeptides, are difficult to treat in solid organ transplant (SOT) recipients as a result of lower effectiveness and high rates of renal impairment. The aim of this study was to evaluate the use of daptomycin in this population. Methods Over a 2‐year period (March 2008–2010) in 9 Spanish centers, we enrolled all consecutive recipients who received daptomycin to treat GPC infection. The study included 43 patients, mainly liver and kidney transplant recipients. Results The most frequent infections were catheter‐related bacteremia caused by coagulase‐negative staphylococci (23.2%), skin infection caused by Staphylococcus aureus (11.5%), and intra‐abdominal abscess caused by Enterococcus faecium (20.9%). The daily daptomycin dose was 6 mg/kg in 32 patients (74.4%). On day 7 of daptomycin treatment, median estimated area under the curve was 1251 μg/mL/h. At the end of follow‐up, analytical parameters were similar to the values at the start of therapy. No changes were observed in tacrolimus levels. No patient required discontinuation of daptomycin because of adverse effects. Clinical success at treatment completion was achieved in 37 (86%) patients. Three patients died while on treatment with daptomycin. Conclusion In summary, daptomycin was a safe and useful treatment for GPC infection in SOT recipients.